The novel «Atonement» by Ian McEwan as an example of postmodern prose - Кушнірова, Тетяна Віталіївна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
In this article discusses the features of the postmodern trends of Ian McEwan prose. Genre novel is a psychological and social novel, based on a comparison of images. Psychological motivations are key in the novel. In the final novel is characterized by postmodern features, which is the dominant image of the author-narrator. It creates individual author myth. The dominant motifs of the novel are: existential motives (decline, aging, loneliness, mother, family), psychological (substitution, sublimation), philosophical (life, death, the meaning of life). Provided genre content, analized genre and style dominants, the main motives. Assigned special role of chronotope, considered their relationship and hierarchy. Highlights features of the individual style of the writer, and the relationship with the literary tradition.